2017
DOI: 10.1248/bpb.b16-00856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Exopolysaccharides Produced by Thermophilic Lactic Acid Bacteria Isolated from Tropical Fruits of Thailand

Abstract: In the present study, we have obtained two exopolysaccharide (EPS)-producing thermophilic lactic acid bacteria (LAB) that were isolated from tropical fruits of Thailand. The two strains, designated LY45 and PY45, were identified as Pediococcus pentosaceus and Lactobacillus amylovorus, respectively. Both plantderived LAB strains, which produce neutral EPSs together with the acidic one, can grow vigorously at 45°C and even at 50°C. Hyaluronidase (EC 3.2.1.35), which catalyzes the degradation of hyaluronic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Isnawati and Trimulyono's (2018) study showed that lactic acid bacteria were able to grow at a range of 4 to 50⁰C. The thermophilic lactic acid bacteria as an EPS producing were not surprising as reported by previous studies (Zhang et al 2011;Panthavee et al 2017;Khanal and Lucey 2018).…”
Section: Isolation and Screening Of Eps-producing Lactic Acid Bacteriasupporting
confidence: 60%
“…Isnawati and Trimulyono's (2018) study showed that lactic acid bacteria were able to grow at a range of 4 to 50⁰C. The thermophilic lactic acid bacteria as an EPS producing were not surprising as reported by previous studies (Zhang et al 2011;Panthavee et al 2017;Khanal and Lucey 2018).…”
Section: Isolation and Screening Of Eps-producing Lactic Acid Bacteriasupporting
confidence: 60%
“…The EPS applied to the skin is predicted to permeate the skin, and the macromolecule may inhibit the enzymatic activity of hyaluronidase, which stimulates the inflammatory reaction. In the previous study, we evaluated the hyaluronidase-inhibitory activity of several LAB-derived EPSs, sodium cromoglicate, dipotassium glycyrrhizinate, and ketotifen fumarate, which are known as substances repressing the type I allergy [12,44,45]. Among those substances, ketotifen fumarate was found not to have detectable anti-hyaluronidase activity [44].…”
Section: Discussionmentioning
confidence: 99%
“…bulgaricus , Leuconostoc species, etc.) have reported synthesizing EPS [ 72 74 ]. Nevertheless, the production of EPS is highly strain-specific behavior and depends on various factors like the composition of the medium, age of the cell, pH, and temperature [ 75 ].…”
Section: The Forms Of Postbiotics and Paraprobioticsmentioning
confidence: 99%